Предмет: Математика,
автор: Belozercava364
0.6 - (1.3x + 1) = 2.8x - 13.52
Ответы
Автор ответа:
6
0.6 - (1.3x + 1) = 2.8x - 13.52
0.6 - 1.3x - 1 = 2.8x - 13.52
0.6 + 13.52 - 1 = 2.8x + 1.3x
13.12=4.1х
х = 3,2
0.6 - 1.3x - 1 = 2.8x - 13.52
0.6 + 13.52 - 1 = 2.8x + 1.3x
13.12=4.1х
х = 3,2
Похожие вопросы
Предмет: Українська мова,
автор: DodoCukHobe3
Предмет: Английский язык,
автор: olgadubnik1984
Предмет: Математика,
автор: Аноним
Предмет: География,
автор: pro100ymnaia
Предмет: Алгебра,
автор: alinaxakimova20